Embattled Vienna 1683/2010: right-wing populism, collective memory and the fictionalisation of politics. (May 2014) - Wodak, Ruth; Forchtner, Bernhard
The victory of a Christian coalition over Ottoman forces besieging Vienna in 1683 marked the beginning of the end of the Ottoman presence in Central and Eastern Europe and the simultaneous rise of the Habsburg Empire in this region. Memories of these events still circulate in present-day Vienna and provide an emotional reservoir for anti-Turkish sentiments. Current tendencies to fictionalise politics support the dissemination of such anti-Turkish narratives in rather unconventional and hybrid genres such as comic-style booklets. In this article, the authors investigate the interplay of collective memories and this hybrid genre within the social context of the fictionalisation of politics through the test case of the Austrian Freedom Party (FPÖ), one of the most successful European right-wing populist parties. By combining multimodal analysis with the discourse–historical approach in critical discourse analysis, they illustrate the ways in which visuals enable the conveying of contradictory meanings through a discursive strategy of calculated ambivalence by blurring past and present, fiction and reality.